Diversidade taxonômica e filogenética de formigas do gênero Pheidole na região do Cerrado - Neves, Karen Christina Ferreira (2016)
The Pheidole genus is recognized for its hyperdiversity. However, little is known about how this diversity is distributed along geographical and environmental gradients. Here are presented the results of a study describing the taxonomic and phylogenetic diversity of Pheidole all over the Cerrado biome of central Brazil. It was used a sampling protocol to collect Pheidole in 26 Cerrado localities. In each place, 120 traps were installed in 30 different sampling points. It was collected a total of 73 morphospecies of Pheidole of which only 17 could be indentified using taxonomic keys. The number of species per site was variable. The most species rich areas tend to be located in the southern and south-eastern regions of the biome. I used multiple regression analysis to assess the influence of five bioclimatic variables (altitude, mean annual temperature, annual temperature amplitude, annual precipitation and precipitation seasonality) and two geographical variables (latitude and longitude) on the Pheidole species richness. The complete model explained 67,4% of the observed Pheidole species richness variation, and the best predictive variables were mean annual temperature, mean annual temperature amplitude, and annual precipitation and latitude. The community composition analyses in each site indicated that the localities situated in the North-east region are less similar than the others. The phylogenetic analyses demonstrated that all communities have an aggregated phylogenetic structure; however there were differences in the degrees of aggregation. The communities located in Mucugê (BA), Águas de Santa Bárbara (SP) and São Carlos (SP) were distinguished from the others in relation to the magnitude of the phylogenetic relationship between the species. According to the multiple regression models, the bioclimatic and geographical variables explained 39,8% of this pattern, and the best predictor variable was the annual precipitation.